The status of Lexicon used in Tabuh Rah ritual in Menyali Village North Bali: An Ethnolinguistic study - Budasi, I Gede; Satyawati, Made Sri; Anggayana, Wayan Agus (Kasetsart Journal of Social Sciences, 2021)
Tabuh Rah (TR) is a cockfighting ritual dedicated to neutralizing the evil spirits by Balinese people. In TR, many specific terms in the lexicon are used by the people involved in the practice. However, since TR is identical to gambling and the national law forbids gambling, the number of people involved in this ritual has decreased. Besides, this ritual is only dominated by adult male villagers. That situation potentially influences the number of lexicon users. Thus, this study aims to identify the lexicon status based on the Expanded Graded Intergenerational Disruption Scale and explain why the lexicon is in a particular position. The researchers collected the data by distributing questionnaires and interviewing the respondents. There were 277 respondents selected in this study. The obtained data were analyzed qualitatively and quantitatively. The results of the study show two significant findings. First, based on the Expanded Graded Intergenerational Disruption Scale, the lexicon is labeled in a threatened position. Only 47 (16.97%) respondents transmitted the lexicon to their children, and the average respondent only understands 50 (70.42%) terms of the exicon from the total 71 terms of the lexicon used in the TR ritual. Second, the lexicon is in threatened status because of the villagers’ overconfidence that the young generation will learn it from the environment, the negative attitude to the lexicon, and the villagers’ belief that such lexicon is masculine. Those situations lead to ignorance of the villagers toward the existence of the lexicon.